TINJAUAN PELAKSANAAN SK GUBERNUR NOMOR 561/K.754/2012 TENTANG UPAH MINIMUM PROPINSI KALIMANTAN TIMUR TAHUN 2013 TERHADAP KARYAWAN KONTRAK DI SAMARINDA - Yohanes B Dasilva (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTIn 1997 , through Law No. 23 of 1997 on Environmental Management ( UUPLH ) in Indonesia has introduced the mechanism of environmental dispute before the court as a representative , the filing of a lawsuit by a small group of people to act on behalf of the community in which a large number of disadvantaged on the basis of similarity of issues , facts and legal claims arising due to pollution and environmental destruction .Civil formal or civil law is the legal rules governing the whole of how to ensure compliance with civil law material by means of the judge . Civil law is needed to regulate how rights claims should be submitted to the court , how the court should examine and give its decision and how the decision of the court should be implemented . Procedural law does not regulate the process of law enforcement outside of court . Although not governed by the procedural law , law enforcement efforts outside the court conducted in a fair and peaceful stay is required , so that the more alternatives that can be chosen by the search for justice in menuntutkan what they are entitled